Audit committee composition and auditor reporting among PN4 companies in Malaysia / Roziani Ali, Syuhaila Razak and Shazalina Mohamed Shuhidan - Ali, Roziani; Razak, Syuhaila; Mohamed Shuhidan, Shazalina (2008)
In the wake of corporate failures following economic crisis starting in 1997, the role of audit committees as corporate governance mechanism has become more important to regulators, the accounting profession and the business community. A research was conducted by Carcello and Neal (2000) to examine the relationship between the composition of audit committee in the financially distressed firm and the likelihood of receiving “going-concern” report for the year 1994. Hence, this study is conducted to examine the similar relationship in Malaysian environment by utilizing the published information for the year 2002. Consistent with the study by Carcello and Neal (2000), this study also found an inverse relationship between the percentage of affiliated directors on audit committee and the likelihood of receiving modified going concern report. However, the relationship is not significant. The result of this study does not support the concerns of the shareholders and Kuala Lumpur Stock Exchange's in having an independent audit committee to ensure the transparency of the financial report. This study concludes that the likelihood of receiving a going concern report for financially distressed firms (PN4 companies) is not significantly affected by the audit committee composition.